PENGARUH PANDEMI COVID-19 TERHADAP MANAJEMEN LABA DAN RELEVANSI NILAI LABA (Studi Empiris pada Perusahaan Consumer Goods yang Terdaftar di Bursa Efek Indonesia Tahun 2018-2021) - Athariq Evan Arianenda; Dwi Ratmono (Diponegoro Journal of Accounting, 2023)
This study aims to analyze the impact of covid-19 pandemic on earnings management and earning value relevance of consumer goods firms in Indonesia in the period of 2018-2021. The independent variable used in this study is covid-19 pandemic. The dependent variable in this study is earnings management and value relevance of earnings. The hypothesis proposed in this study is that the covid-19 pandemic has an effect on earnings management and the covid-19 pandemic has a negative effect on the value relevance of earnings.This study used samples from 43 consumer goods firms in Indonesia which presented their financial reports on the IDX and yahoo finance sites within 2018-2021 period. The data used in this study is secondary data and the sampling used is purposive sampling method. To test the hypothesis, this study uses panel data regression analysis as the main test and multiple and simple regression analysis as additional analysis to examine the increase and decrease in the value relevance of earnings through the reduction of the adjusted r2 value of the two models contained in the Collins model.The results of this study indicate that covid-19 pandemic has a significant negative effect on earnings management and the value relevance of earnings. Therefore, it can be concluded that the company has proven to practice earnings management by doing income-decreasing earning management in the covid-19 pandemic year and the covid-19 pandemic reduced the value relevance of earnings as accounting information.